(3EYGOI JfXje GdEbJUGO GdhWfjs - (3eMeO HdbGSe MSf(B, (3Hgdhds ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 1993)
(3GdeNWW GdNeGSj GdGhd ddJfejI (B1980-1984- (3JMdjd GfLGR GdeNWW GdNeGSj GdChd GdaUd GdSGHY(B- (3GdeNWW GdNeGSj GdKGfj ddJfejI (B1985-1989 -(3eejRGJ JNWjW GdJfejI hJhLgGJgG GdLOjOI(B.s
Keywords: (3GdJNWjW GdGbJUGOjs; (3GdJfejI GdEbJUGOjI(B- (3GdLRGFQs; (3GdLRGFQ(B- (3GdSjGSI GdEbJUGOjIs